Paciente Pediátrico Femenino de 10 Años de edad con Asma Bronquial - Andrade Tacle, Evelyn Gabriela (2021)
Asthma is a respiratory disease whose name derives from the Greek asthma. It is characterized by episodes, of varying intensity and frequency, in which the affected person has difficulty breathing, accompanied by high-pitched sounds, similar to a whistle. These episodes or attacks are triggered by an allergic reaction in the airways that causes various agents to produce inflammation in the bronchi, making it difficult for air to pass into the lung. In addition, secretory cells, present throughout the respiratory system, begin to produce more mucus. Consequently this forms plugs that make breathing even more difficult.